Vehicle-Based Evaluation of 12-V SLI Battery Cranking Performance under Ambient Cold-Start and Hot-Start Conditions - Ichsan Nasution; M. Sadly Firmansyah; M. Yasep Setiawan; Yuli mafendro dedet eka saputra; Budi Utomo Wisesa; Ilham Febriansyah (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2026)
Reliable engine starting in conventional vehicles depends on the SLI battery’s ability to deliver high cranking current while maintaining voltage under load. This study evaluated a 12-V maintenance-free lead-acid SLI battery rated at 450 A CCA under practical ambient cold-start (20–30 °C) and hot-start (85–105 °C) conditions. Testing was conducted over four consecutive days using measured CCA, CCA ratio, minimum cranking voltage, open-circuit voltage (OCV), and starter duration. The tested battery showed generally better cranking indicators under the hot-start condition, with higher measured CCA, higher CCA ratio, slightly higher minimum cranking voltage, and shorter average starter duration. OCV remained stable at approximately 12.5–12.6 V, indicating that the observed cranking differences were not mainly associated with major no-load voltage variation. The combined use of CCA, cranking voltage, OCV, and starter duration provides a practical diagnostic basis for evaluating SLI battery starting readiness.